Neural Responses to Social Reward Predict Depressive Symptoms in Adolescent Girls During the COVID-19 Pandemic. (16th July 2021) - Sequeira, Stefanie L; Silk, Jennifer S; Hutchinson, Emily; Jones, Neil P; Ladouceur, Cecile D
Abstract: Objective: Adolescent depression is increasing during the COVID-19 pandemic, possibly related to dramatic social changes. Individual-level factors that contribute to social functioning, such as temperament and neural reactivity to social feedback, may confer risk for or resilience against depressive symptoms during the pandemic. Methods: Ninety-three girls (12–17 years) oversampled for high shy/fearful temperament were recruited from a longitudinal study for a follow-up COVID-19 study. During the parent study (2016–2018), participants completed a functional magnetic resonance imaging task eliciting neural activity to performance-related social feedback. Depressive symptoms were assessed during the parent study and COVID-19 follow-up (April–May 2020). In 65 participants with complete data, we examined how interactions between temperament and neural activation to social reward or punishment in a socio-affective brain network predict depressive symptoms during COVID-19. Results: Depressive symptoms increased during COVID-19. Significant interactions between temperament and caudate, putamen, and insula activation to social reward were found. Girls high in shy/fearful temperament showed negative associations between neural activation to social reward and COVID-19 depressive symptoms, whereas girls lower in shy/fearful temperament showed positive associations. Conclusions: Girls high in shy/fearful temperament with reduced neural activation to social reward may be less likely to engage socially, which could be detrimental during the pandemic when social interactions are limited. In contrast, girls lower in shy/fearful temperament with heightened neural reactivity to social reward may be highly motivated to engage socially, which could also be detrimental with limited social opportunities. In both cases, improving social connection during the pandemic may attenuate or prevent depressive symptoms.